Organização da informação de coleções musealizadas - Victor Pinheiro Louvisi (2014)
The information about collections of museum can be seen within a set of coordinated actions which aims to preserve material evidence produced or collected by humans. The documentation generated by the museums is very broad, ranging from the legal procedures for the acquisition of the piece, the restoration interventions, exhibitions, loans and more. There is a potential that such information may be in the generation of new information, helping professionals in the planning and execution of their work. In addition, this information is important testimonies about the history of these collections and institutions that hold them. Thus, the study aims to approach the organization of dedicated information for the work done in museums, focusing on the systemic character of museum institutions. For the development of research, we chose a horizontal approach to museum activity, identifying its processes from the one that removes the object from its original function to perform a symbolic function, turning it into musealized cultural property; then discusses the inclusion of the object in a collection through the technical processing to the guard at the technical reserve and its fruition through the exhibition, educational activities, as well as, any shares of conservation and restoration. Discusses the concepts, methods and organization tools for information to treat the information produced by the museum and its relationship with the museum documentation. These standards being discussed to standardize the actions taken by the museum institutions. Discusses the concepts of musealization, document, heritage and cultural assets, watching their relations with the subject matter. It also discusses the documentary production held by the museum and addresses, for example, some institutions working systemically its collection, as the case of the Imperial Museum of Petropolis, the Magnes Collection of Jewish Art and Life and the Smithsonian Institute. Finally we conclude that museums hold a huge amount of content, often heterogeneous, and that the information on the collections are dispersed and may be in multiple locations within the same institution, undermining the management of collections and jamming the information flow. To avoid this, the museum should be seen in a systemic way and to use the new information technologies to assist in this work of management and information integration and the museum's actions.